Reconstructing Human-Centered Islamic Educational Leadership in the Artificial Intelligence Era - Moh. Khoiruddin; Indah Wahyuni; Uswatun Chasanah; Masyhadi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to various aspects of human life, including the field of Islamic education. The implementation of AI in educational governance offers substantial opportunities for administrative efficiency, personalized learning, and data-driven decision-making optimization. However, the dominance of technology also poses serious challenges, including the decline of humanistic dimensions, spirituality, empathy, and interpersonal relationships within the educational process. This study aims to reconstruct human-centered Islamic education management as a response to the dominance of Artificial Intelligence. The research employs a qualitative approach using a library research method through the analysis of scientific journals, books, and academic documents related to Islamic education management, human-centered education, and Artificial Intelligence. The findings reveal that the reconstruction of human-centered Islamic education management should be developed through five main aspects: strengthening spiritual leadership, integrating technological ethics, revitalizing the culture of empathy in learning, reinforcing tawhid values in educational governance, and developing a collaborative educational system based on humanistic technology. This study confirms that AI cannot replace the humanistic role of teachers and spiritual values in Islamic education. Therefore, the human-centered approach becomes an essential foundation for maintaining balance between technological advancement and the objectives of Islamic education oriented toward the formation of insan kamil. The development of Artificial Intelligence (AI) has brought significant changes to various aspects of human life, including the field of Islamic education. The implementation of AI in educational governance offers substantial opportunities for administrative efficiency, personalized learning, and data-driven decision-making optimization. However, the dominance of technology also poses serious challenges, including the decline of humanistic dimensions, spirituality, empathy, and interpersonal relationships within the educational process. This study aims to reconstruct human-centered Islamic education management as a response to the dominance of Artificial Intelligence. The research employs a qualitative approach using a library research method through the analysis of scientific journals, books, and academic documents related to Islamic education management, human-centered education, and Artificial Intelligence. The findings reveal that the reconstruction of human-centered Islamic education management should be developed through five main aspects: strengthening spiritual leadership, integrating technological ethics, revitalizing the culture of empathy in learning, reinforcing tawhid values in educational governance, and developing a collaborative educational system based on humanistic technology. This study confirms that AI cannot replace the humanistic role of teachers and spiritual values in Islamic education. Therefore, the human-centered approach becomes an essential foundation for maintaining balance between technological advancement and the objectives of Islamic education oriented toward the formation of insan kamil.